An ultra wideband antenna for Ku band applications - Aziz El fatimi; Seddik Bri; Adil Saadi (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This paper presents a candidate ultra wideband antenna for Ku-band wireless communi- cations applications, analyzed and optimized by the finite element method (FEM). This three-dimensional modeling was realized and compared with published antennas for val- idate the performances of the proposed antenna. Its design is based on the insertion o fseveral symmetrical slots of different sizes on the ground plane of a mono-layer patch antenna to overcome the main limitation of the narrow bandwidth of patch antennas. The proposed antenna, made on an FR-4 epoxy mono-layer substrate with a defected ground plane (dielectric constant εr = 4,4, loss tangent tan δ = 0,02 and thickness hs = 1.6 mm). The simulated numerical results obtained are very satisfying; Bandwidth = 10.48 GHz from f1 = 9.34 GHz to f2 = 19.82 GHz, S11 = -34.17 dB, Voltage Stationary Wave Ratio VSWR = 1.04 , Gain = 6.27 dB.